Effects of internal and external factors on internet-based digital technology usage by SMEs in a developing country - Azam, Shah; Quaddus, Mohammed (International Information Management Association, 2012)
This paper analyses the effects of culture and environment on the adoption and use of Internet based digital technology (IBDT) by small and medium sized enterprises (SMEs) from a developing country perspective. A structural equation modeling is finally employed within a mix method research setting with a cross-sectional dataset of 557 SMEs in Bangladesh. The study reveals a significant association of normative pressures, coercive pressures, power distance, in-group collectivism, Bengali values, perceived usefulness, and perceived ease of use with SMEs intention to use IBDT while intention significantly affects actual usage behavior. The study concludes with some implications of the results.